Makings of the sea : journey, doubt and nostalgia - Baldacchino, John (On Mediterranean aesthetics ;, 2010)
Makings of the Sea is an inquiry into the makings of the Mediterranean imagination in the 20th century, focusing on specific cases in the visual and performing arts, music and literature. It also questions a number of populist perceptions of the Mediterranean and its cultures. Following a thematic structure that falls broadly under the headings of journey, doubt and nostalgia, this is an essay on Mediterranean aesthetics.